PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEKNIK BERTUKAR PASANGAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TATA NAMA SENYAWA DAN PERSAMAAN REAKSI DI KELAS X SMA NEGERI 14 PEKANBARU - Mita Fresandi; Roza Linda; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research aims to increase student learning achievement on the subject compounds nomenclature and chemical reaction equation of elements in class X SMAN 14 Pekanbaru. This research was of experiment research with pretest-posttest design. The research was conducted in SMAN 14 Pekanbaru. The samples of this research were the students of class X.4 as the experimental class and students of class X.3 as the control class. In experimental class was applied cooperative learning model type pair exchange technique, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tcount>ttable is 6,41 > 1,67 means that the application of model cooperative learning type pair exchange can improve student achievement on the subject compounds nomenclature and chemical reaction equation of elements in class X SMAN 14 Pekanbaru increase learning achievement category in the experimental class is based on the normalized gain score (N-Gain) relatively high at 0,73.Keywords: Cooperative Learning, Pair Exchange, Learning Achievement, Compounds Nomenclatur and Chemical Reaction Equation